1q21 Gain Combined with High‐Risk Factors Is a Heterogeneous Prognostic Factor in Newly Diagnosed Multiple Myeloma: A Multicenter Study in China. (27th August 2019) - Li, Xiaozhe; Chen, Wenming; Wu, Yin; Li, Jianyong; Chen, Lijuan; Fang, Baijun; Feng, Ying; Liu, Junru; Chen, Meilan; Gu, Jingli; Huang, Beihui; Li, Juan
Abstract: Background: The prognostic value of 1q21 gain in newly diagnosed multiple myeloma (NDMM) remains controversial. Our aim was to investigate the prognostic value of 1q21 gain in a Chinese population. Materials and Methods: We retrospectively identified 565 patients with NDMM from multiple centers in China. Results: We detected 1q21 gain in 222 (39.3%) patients, among whom 144 had three copies of 1q21, 57 had four copies of 1q21, and 21 had at least five copies of 1q21. Copy number variation did not show any effect on the disease outcome. Multivariate analysis indicated that 1q21 gain was an independent factor for poor prognosis, but we found that 1q21 gain was strongly associated with other high‐risk factors, such as del(17p), t(4;14), t(14;16), lactate dehydrogenase (LDH) level >300 U/L and International Scoring System (ISS) stage II–III ( p < .001). Further analysis revealed that in the absence of other high‐risk factors, isolated 1q21 gain resulted in similar progression‐free survival (PFS; 52.0 vs. 52.8 months, p = .810) and overall survival (OS; not reached vs. not reached, p = .833); additionally, when present with other high‐risk cytogenetic abnormalities or increased LDH levels, 1q21 gain lost its prognostic power. However, the presence of 1q21 gain increased the adverse impact of ISS stage. Furthermore, 1q21 gain predicted poor PFS and OS in patients who received bortezomib‐based regimens. Moreover, autologous stem cell transplantation reversed the poor prognosis in patients with 1q21 gain. Conclusion: Our results show that heterogeneity exists among patients with 1q21 gain and suggest that we should assess the impact of 1q21 gain on prognosis according to different treatment regimens and accompanying high‐risk factors. Implications for Practice: 1q21 gain is one of the most common chromosomal aberrations in multiple myeloma (MM); however, the prognostic value of 1q21 gain remains controversial. This study investigated the prognostic value of 1q21 gain in a Chinese population with newly diagnosed MM. The results showed that heterogeneity exists among patients with 1q21 gain and suggested that the impact of 1q21 gain on prognosis should be assessed according to different treatment regimens and accompanying high‐risk factors. These results could help stratify risk in patients with MM and guide treatment decisions. Abstract : The identification of prognostic factors for multiple myeloma is important. This article focuses on the prognostic value of 1q21 gain in a Chinese population according to different treatment regimens and accompanying high‐risk factors.